2013
DOI: 10.1093/pcp/pct001
|View full text |Cite
|
Sign up to set email alerts
|

ERISdb: A Database of Plant Splice Sites and Splicing Signals

Abstract: Splicing is one of the major contributors to observed spatiotemporal diversification of transcripts and proteins in metazoans. There are numerous factors that affect the process, but splice sites themselves along with the adjacent splicing signals are critical here. Unfortunately, there is still little known about splicing in plants and, consequently, further research in some fields of plant molecular biology will encounter difficulties. Keeping this in mind, we performed a large-scale analysis of splice sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 58 publications
4
54
0
Order By: Relevance
“…36 We analyzed the splice sites of 2,806 rice circRNAs identified in this study. The full-length sequences of some circRNAs could not be exactly mapped to a certain genome position showing several bases shuffling.…”
Section: Alternative Circularization Of Circrnas In Ricementioning
confidence: 99%
See 1 more Smart Citation
“…36 We analyzed the splice sites of 2,806 rice circRNAs identified in this study. The full-length sequences of some circRNAs could not be exactly mapped to a certain genome position showing several bases shuffling.…”
Section: Alternative Circularization Of Circrnas In Ricementioning
confidence: 99%
“…36 Szabo et al (2015) first found a small portion of U12-dependent circRNAs in humans. 30 Besides backsplicing reads, our method predicts circRNAs mainly depending on full-length sequence acquisition rather than filtration by the GT/AG splicing signals.…”
mentioning
confidence: 99%
“…The repeated sequence may contribute to conformational changes, making the promoter more accessible for transcription factors and RNA polymerase II [62], or facilitating the interaction of splicing factors with upstream transcription factors [27]. Alternatively, the repeated sequence possibly contained regulatory sequences involved in IME; however, we were not able to identify any candidate intron regulatory sequences using ERISdb [63], possibly due to the limited knowledge of intron regulatory elements in plants. Nevertheless, we found that the repeated sequence was T-rich, with T-nucleotides accounting for more than 40% of the whole sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The predicted branch point sequences for both Arabidopsis thaliana and Oryza sativa (brach_ download.gz) were downloaded from Database of Plant Splice Sites and Splicing Signals (http://lemur.amu.edu.pl/share/ERISdb/ home.html) (Szcześniak et al 2013). NCBI BLASTN was used to search for sequences complementary to the 24-nt sutr-siRNAs smRNA sequences.…”
Section: Isolation and Analysis Of Sutr-sirna Targetsmentioning
confidence: 99%